HUBUNGAN PRAKTIK HIGIENE PENJAMAH DENGAN KUALITAS MIKROBIOLOGIS PADA JAJANAN SIOMAY DI KECAMATAN TEMBALANG KOTA SEMARANG - Azizah, Hana Fitria; Martini, Martini; Purwantisari, Susiana (Jurnal Kesehatan Masyarakat (Undip), 2017)
Siomay is a mixed food that has a limit of colony growth 1 x 104 colony/g or mL. A fish or meat-based food such as siomay is easily contaminated by pathogenic bacteria such as Escherichia coli. The contamination on siomay could be caused by the hygiene practices of food that was not applied properly. This research aimed to analyze the association between hygiene practices and microbiological quality of siomay stall in Tembalang Sub-District. The type of this research was analytic observasional study with cross-sectional approach. The population of this research was all of the siomay stall in Tembalang Sub-District. Sampling procedure used accidental sampling technique and it was obtained 37 samples. Interview and observation were conducted on hygiene practices, raw materials quality and raw materials storage practices at siomay stall. The data were analysed using chi square test. The results revealed that samples of 73% had the MPN values exceeding the limit, 70,3% was contaminated Escherichia coli exceeding requirement, and 32,4% was grown yeast exceeding the standards, then 91,9% samples did not supply the microbiological quality of food. The analysis showed that there was an association between hygiene practice (p = 0,047) in siomay stall with the microbiological quality. However, the raw materials quality and the raw materials storage practices of siomay had been quite good.